Configuring advanced Windows server 2012 R2 services training guide - Thomas, Orin 1973- (Microsoft Press, 2014)
Fully updated for Windows Server 2012 R2! Designed to help enterprise administrators develop real-world, job-role-specific skills - this Training Guide focuses on configuration of advanced services in Windows Server 2012 R2. Build hands-on expertise through a series of lessons, exercises, and suggested practices - and help maximize your performance on the job. This Microsoft Training Guide : Focuses on job-role-specific expertise for advanced configuration tasks Fully updated for Windows Server 2012 R2, including new practices Provides in-depth, hands-on training you take at your own pace Creates a foundation of skills which, along with on-the-job experience, can be measured by Microsoft Certification exams such as 70-412 Topics include: Advanced Active Directory Infrastructure Active Directory Sites and Replication Advanced DHCP and DNS Active Directory Certificate Services Backup and Recovery Advanced File Services and Storage High Availability Site Resilience Dynamic Access Control and Active Directory Rights Management Services Active Directory Federation Services.
Includes index. - Online resource; title from title page (Safari, viewed June 2, 2014)
Keywords: Microsoft Windows server; Client/server computing; Computer networks; Computer Communication Networks; Architecture client-serveur (Informatique); Réseaux d'ordinateurs; COMPUTERS; Operating Systems; Windows Server; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference